Indigenous Land Ownership and Title in Canada: Implications for a Northern Corridor - Cherie Metcalf (The School of Public Policy Publications, 2023)
The proposal to create a Northern Corridor that would allow for cross-country, multi-modal infrastructure development is an ambitious vision (Sulzenko and Fellows 2016; Standing Senate Committee 2017). This proposed infrastructure corridor would incorporate multiple uses, from pipelines to railways, roads, telecommunications, electricity infrastructure and more. Its geographic scale stretches continuously from coastal B.C. across Canada to the Atlantic coast, with spurs running northward to the Arctic Ocean through the Northwest Territories, Nunavut and via Manitoba to Hudson’s Bay. A critical foundation for its successful development will be the ability to appreciate and incorporate the rights of Indigenous peoples affected by the project (Wright 2020; Newman 2022). The goal of this research paper is to outline the law of Indigenous peoples’ land ownership rights, including proven and asserted title, Crown-Indigenous treaty relations and obligations and Indigenous land claims agreements, and to consider the implications for a large-scale infrastructure project like the Northern Corridor.1 The focus is on the legal and regulatory aspects of Indigenous peoples’ land rights within the non-Indigenous Canadian legal system.2 The research paper uses standard legal methods to assess the land ownership rights of Indigenous peoples, drawing on relevant constitutional and statutory provisions, leading cases and secondary literature. The paper proceeds with a brief overview of these distinct types of Indigenous land rights, then provides a more detailed account of the legal content of s. 35 constitutional Aboriginal title, historic and modern treaty rights. This includes discussion of government’s legal duty of consultation and accommodation, and the requirements for constitutionally justified limitation of these rights. Indigenous land ownership rights in reserve lands are also discussed. A series of case studies more fully illustrates the implications of these varied Indigenous land rights for a project like the Northern Corridor. Finally, the paper turns to the dynamic nature of Indigenous rights and the potential influence of the UNDRIP.